The cave of the cyclops : Mesolithic and Neolithic networks in the northern Aegean, Greece ; Vol. 2: Bone tool industries, dietary resources and the paleoenvironment, and archeometrical studies (Prehistory monographs, 2010)
10 Sequential Radiocarbon Dating and Calculation of the Marine Reservoir Effect11 Clastic Sediments; 12 Stable Isotopic Analysis of the Mollusk Shells; Index.